Role of respiratory NADH oxidation in the regulation of Staphylococcus aureus virulence - Schurig‐Briccio, Lici A (EMBO Rep, 2020)
The success of Staphylococcus aureus as a pathogen is due to its capability of fine‐tuning its cellular physiology to meet the challenges presented by diverse environments, which allows it to colonize multiple niches within a single vertebrate host. Elucidating the roles of energy‐yielding metabolic pathways could uncover attractive therapeutic strategies and targets. In this work, we seek to determine the effects of disabling NADH‐dependent aerobic respiration on the physiology of S. aureus. Differing from many pathogens, S. aureus has two type‐2 respiratory NADH dehydrogenases (NDH‐2s) but lacks the respiratory ion‐pumping NDHs. Here, we show that the NDH‐2s, individually or together, are not essential either for respiration or growth. Nevertheless, their absence eliminates biofilm formation, production of α‐toxin, and reduces the ability to colonize specific organs in a mouse model of systemic infection. Moreover, we demonstrate that the reason behind these phenotypes is the alteration of the fatty acid metabolism. Importantly, the SaeRS two‐component system, which responds to fatty acids regulation, is responsible for the link between NADH‐dependent respiration and virulence in S. aureus.